2020
DOI: 10.1038/s41598-020-59874-8
|View full text |Cite
|
Sign up to set email alerts
|

Egg genotyping reveals the possibility of patent Ancylostoma caninum infection in human intestine

Abstract: Hookworms are intestinal parasites that cause major public health problems, especially in developing countries. To differentiate eggs from different hookworm species, it is necessary to use molecular methodologies, since the eggs are morphologically similar. Here, we performed the molecular identification of single hookworm eggs from six Brazilian states. Of the 634 eggs individually analyzed, 98.1% (622/634) represented Necator americanus, and surprisingly, 1.9% (12/634 eggs from the same patient) represented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 54 publications
1
25
0
1
Order By: Relevance
“…The main species of feline Ancylostoma found in North America are Ancylostoma tubaeforme and Ancylostoma braziliense [10]. Since feline Ancylostoma and T. cati are zoonotic parasites [11][12][13][14][15][16][17][18], it is important to conduct routine fecal examinations of cats, and treat them as necessary to maintain their wellness and that of their owners.…”
Section: Introductionmentioning
confidence: 99%
“…The main species of feline Ancylostoma found in North America are Ancylostoma tubaeforme and Ancylostoma braziliense [10]. Since feline Ancylostoma and T. cati are zoonotic parasites [11][12][13][14][15][16][17][18], it is important to conduct routine fecal examinations of cats, and treat them as necessary to maintain their wellness and that of their owners.…”
Section: Introductionmentioning
confidence: 99%
“…Ancylostoma caninum cause haemorrhagic enteritis in young puppies and chronic irondeficiency anaemia in older dogs (Georgi et al, 1969), while in humans it causes cutaneous larva migrans and eosinophilic enteritis (Bowman et al, 2010). A few studies have reported the presence of A. caninum eggs/DNA in human faeces; however, it remains uncertain if these were natural infections or inadvertent passage, as non-patent worms of this species were detected in human intestines previously (George et al, 2016;Ngcamphalala et al, 2019;Furtado et al, 2020).…”
Section: Genotyping Of Helminths By Pcr Restriction Fragment Length Polymorphism (Rflp) and Sequencingmentioning
confidence: 99%
“…Although most infections are asymptomatic, a single immature adult worm residing in the small intestine of humans is capable of eliciting abdominal pain, intestinal bleeding, diarrhoea and weight loss as a result of eosinophilic enteritis and aphthous ileitis (Prociv and Croese, 1990). There is growing evidence suggesting that occasionally, patent, egg-producing infections may also occur in humans (Furtado et al, 2020).…”
Section: Gondii C Sinensis O Viverrini Paragonimus Spp and Gnathostoma Spinigerum)mentioning
confidence: 99%